Linking relationship quality and resourcefulness to group performance. Issue 3 (4th March 2019) - Nasim, Kanwal; Iqbal, Muhammad Zahid Zahid
Abstract : Purpose: The purpose of this paper is to know that how group resources (internal and external) and the relationship quality among group members relate to group performance. Design/methodology/approach: Given the normative nature of group performance, the study is carried out in a contrived environment. Participants were 204 master of business administration students who were allocated to 51 study groups. Data were collected in three waves and from two different sources, i.e., students and instructors. Data analysis was carried out by employing regression analysis and the bootstrapping procedure, i.e., PROCESS. Findings: The results of this paper reveal that an individual-level internal resource, i.e. time, positively predicts group performance, while group-level internal resources, i.e., group composition and group members' experience, negatively predict group performance. Both external resources (external communication and instructor's support) are found to have a positive effect on group performance. The relationship quality among group members partially relates to group performance. Instructor's support as an external resource is found to moderate the relationship between only two aspects of relationship quality and group performance. Practical implications: This study provides guidance to group members as to how they can utilize internal and external group resources and their relationship quality for enhancing their group performance. Managers in varied organizations can also utilize the findings of this study. Originality/value: This study is unique in that it offers a new insight into internal and external resources and relationship quality, that is, from the perspective of group performance. The group resources included in the study are rarely found in the existing literature.